Olive, Again - Book 2 Book 2 - Strout, Elizabeth (New York : Random House, 2019)
"Olive Kitteridge has returned, as indomitable as ever ... this time as a person getting older, navigating her next decade as she comes to terms with the changes--sometimes welcome, sometimes not--in her own life. Here is Olive, strangely content in her second marriage, still in an evolving relationship with her son and his family, encountering a cast of memorable characters in the seaside town of Crosby, Maine. Whether its a young girl coming to terms with the loss of her father, a young woman about to give birth at a baby shower, or a nurse who confesses a secret high school crush, the irascible Olive improbably touches the lives of others"--
Keywords: Older women -- Fiction; Retired teachers -- Fiction; Interpersonal relations -- Fiction; City and town life -- Maine; Fiction; Adult fiction